Management Simulasi Jaringan Wireless dan Management Bandwdith dengan Metode Firewall Mangle dan Queue Tree untuk Priority Traffic - Andi Suprianto; Ahmad Ainurridho (JURNAL REKAYASA INFORMASI, 2022)
This research aims to improve the quality of wireless networks and optimize bandwidth or internet speed. Based on the initial analysis conducted, the unstable quality and not optimal bandwidth obtained due to the absence of bandwidth management on the network. Based on literature studies, the solution to improve wireless network quality and optimize bandwidth is to add bandiwidth management configuration using the mangle firewall method and queue tree in Mikrotik Router. Simulation is done by adding the configuration so that the bandwidth obtained by each user will be more optimal. Keywords: Main Link, Backup Link, Mpls-Vpn, Routing Bgp, Aspath Prepend,Wireless, Bandwidth, Firewall Mangle, Queue Tree, Mikrotik